RANCANG BANGUN ESTIMATOR WAKTU OPERASIONAL DAN MANAJEMEN BEBAN LISTRIK PADA DC HOUSE - Dzulfikar Ontoseno; Akhmad Zainuri; Onny Setyawati (Jurnal Mahasiswa TEUB, 2023)
Solar panels is a renewable energy generator that utilizes energy from sunlight. One example of its application is the DC House. The working system of solar panels in DC homes is not much different from solar panels in general. Batteries have an important role in the PLTS system. In the utilization of the battery there are several things that need to be considered including the discharge limit and charging limit in the form of usage cycles. If there is a discharge process or an overcharging process, it can cause damage to the battery. So we need a system that can prevent these things from happening, one of which is by implementing a feature to determine the estimated operational time of the battery and electrical load management. This study discusses the design of estimator tools and managing electrical loads in DC Houses. The design of this tool includes time estimation, current sensor, voltage sensor and microcontroller as automatic load control. The current sensor and voltage sensor data taken from the test object, namely the battery, the incoming and outgoing energy will be known. This energy will later be used to determine the estimated operational time and also used as a parameter for automatic load control. When the battery energy is below the discharge limit, the microcontroller will give an order to cut off the electrical energy flowing to the load. So with this system will prevent the use of electrical energy that is not reasonable. The results of this study found that the level of accuracy on the voltage sensor 1 was 97.97% and the accuracy level on the voltage sensor 2 was 98.91%. Then the level of accuracy on the current sensor ACS712-30A is 97.44% while on the current sensor ACS758-100A the level of accuracy is 93.32%. The results of making this operational time estimator system have an accuracy rate of 97.43% and the electrical load management is functioning properly according to the program. Keywords: battery, time estimator, sensor, electrical load management, DC House